Kitab Kuning of Shafi’i School in Teaching Fiqh at Pondok Pesantren in South Kalimantan amid Islamic Transnational Movement - Muthmainnah, Inna; Rasyidi; Syaiful, Muhammad; Wulansari, Herida (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – In curriculum studies, teaching materials are fundamental components. In the context of Islamic education, especially in pondok pesantren, kitab kuning has long been the main reference, particularly in fiqh and uṣūl al-fiqh, that according to Bruinessen represents Shafi’i school. Yet in the last few decades, Islamic transnational movement that has introduced diverse schools of thought has entered Indonesia, potentially including the educational area. However, previous studies have not touched kitab kuning at pondok pesantren in particular. This study therefore examines whether Bruinessen’s finding regarding the dominance of Shafi’i school in fiqh and uṣūl al-fiqh remains valid at pondok pesantren in South Kalimantan or has shifted, especially concerning kitab kuning. Design/methods/approach – The study employed qualitative case study, with documentation and interview in data collection. Kyais and ustādhs at five pondok pesantren salafiyah, khalafiyah, and mixed across two regencies in South Kalimantan were involved. Miles’ and Huberman’s data analysis was followed while Lincoln and Guba’s trustworthiness in terms of triangulation of methods of data collection, sources of data, member checking, an audit trail, reflexivity, and thick description were used. Findings – The study concluded that salafiyah and mixed pondok pesantren continued to teach kitab kuning of the Shafi’i school as their teaching materials in fiqh and uṣūl al-fiqh. Although some new references were introduced, they were still in Shafi’i school. In addition, the kyais and ustādhs read kitab kuning from other schools, they did not teach them to their santris citing the absence of ijāzah, and to preserve Ahlussunnah wa al-jamā’ah. They studied those kitab kuning only for personal enrichment. At pondok pesantren khalafiyah, initially the santris studied fiqh from four schools of fiqh, however later they learnt solely Shafi’i school, as available ustadzs were trained in that school. Thus, Islamic transnational movement has not touched pondok pesantren’s teaching materials. Research implications – This study was limited to two regencies in South Kalimantan. For generalization, like Bruinessen’s research, broader study is required.